Kurrachee, past, present and future - Baillie, Alexander F.; Lari, Yasmeen (Karachi : Oxford University Press, 1997)
Includes an introd. to 1997 ed. by Yasmeen Lari.
Reprint, with added t.p. of 1890 ed. published by Thacker, Spink, Calcutta.
Includes bibliographical references.
Keywords: Karachi (Pakistan) -- History